ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN LAPTOP MEREK ACER - Rizka Noor Baiti Rakhma, 08.05.51.0058; Widyasari, Suzy (Students Journal of Economic and Management, 2012)
Laptop is more often used in recent years because of the ease and practicality, as well as reasonable prices. Suit their needs and wants, the consumer makes a purchase a laptop because the laptop consists of a wide selection of brands and the quality of the consumer laptop should consider the brand and the quality of what is desirable in order to satisfy the product purchased and its use in accordance with the wishes and need. There are five hypothesis tested in this study,the fourth hypothesis are tested as partialy test, explain about product, price, promotion, and trust in brand on purchasing decision, and last hypothesis use simultant test, explain about product, price, promotion, and trust in brand on purchasing decision do simultantly. Samples used in this study 80 respondents to the sampling technique was purposive sampling is sampling technique sample with certain criteria. The data used are the primary data and secondary data analysis using qualitative and quantitative analyzes covering validity, reliability testing, regression analysis, determination coefficient and hypothesis test that includes a t test and F test. Based on data analysis and test the hypothesis from the partialy test the results variable product, price, promotion, and brand trust has a positive and significant influence on Acer laptop purchasing decisions. Variable product, price, promotion, and trust in brand simultantly significant and positive influence on purchase decisions Acer laptop.The most variable which is influenced to the purchasingdecision making is promotion from the four variables.Key words: Product, Price, Promotion, Trust in Brand, Purchasing Decision.